Higher Education Institutions in Bosnia and Herzegovina: Usage of Social Network Sites - Mirela Mabić; Dražena Gašpar; Jelena Zovko (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
The paper presents the research of the current state of the presence and activities of higher education institutions in Bosnia and Herzegovina (BiH) on social network sites (SNS). Although higher education institutions in BiH have recognized the necessity of using social networks for communications with their stakeholders, especially students, they still struggle with the content posted on SNS and its frequency. The authors use content analysis to examine SNS posts from BiH higher education institutions and engagement from their constituents on these posts. Results show that there are significant differences in engagement received on posts across institution type and according to content and type of posts. The aim of the paper is to analyze if HEIs in BiH use SNS and to what degree, as well as if there is any difference between public and private institutions related to the usage of SNS.
Keywords: I2; O39; 330; social networks sites; higher education institutions